Unemployed Graduates: Entrepreneurship Education Influences Entrepreneurial Intentions in Zimbabwe - Wilson Mabhanda; Abigirl Mawonedzo (Journal of Sustainable Tourism and Entrepreneurship, 2026)
Purpose: Given the high unemployment rate, this study investigates the empirical significance of Entrepreneurship Education (EE) in shaping the entrepreneurial intentions of Zimbabwean graduates, addressing a critical policy gap regarding the efficacy of the local EE curriculum. Research Methodology: The interpretivist philosophy served as the foundation for collecting qualitative data using a descriptive multi-case study method, along with thematic analysis techniques in the Midlands Province. A total of 20 participants, selected through purposeful and snowball sampling, took part in face-to-face interviews and focus group discussions. Results: The findings show that exposure to entrepreneurship education plays a significant and positive role in boosting graduates' ambitions and inclination towards self-employment. EE content, particularly when focused on opportunity identification and skill leveraging, acted as a catalytic agent, encouraging graduates to re-evaluate and pursue entrepreneurial paths based on their existing vocational and general skills. Conclusions: This study conclusively demonstrates that entrepreneurship education significantly influences and boosts the entrepreneurial intentions and self-employment inclination of unemployed graduates in Zimbabwe by enabling them to leverage their existing skills. This suggests that a well-designed EE curriculum can be a powerful, proactive policy tool for shifting graduates’ career mindsets. Limitations: Qualitative data from one university and polytechnic in Gweru restrict generalizability to other Zimbabwean cities or institutions. Contributions: To combat graduate unemployment, this study provides a framework for Zimbabwean officials to strengthen the national entrepreneurship curriculum. The study highlights the necessity of prioritising hands-on experience and opportunity recognition over theoretical learning, thereby contributing to the broader goal of fostering a sustainable, local entrepreneurial ecosystem.